The Role of The Church in Building the Economy of The Congregation Members of The Protestant Christian Church in Bali (Case Study at The Protestant Christian Church in Bali) - Yurianta, I Wayan Dedik; Junaedi, I Wayan Ruspendi; Trimurti, Christimulia Purnama; Utama, I Gusti Bagus Rai (The Es Economics and Entrepreneurship, 2025)
This research examines the role of the Protestant Christian Church in Bali (GKPB) in building the economy of its congregation members, a theme that is still rarely explored empirically in Indonesia, particularly in the local context of Bali. The background of this research is based on the strategic role of the church not only as a spiritual center but also as an agent of community economic empowerment. Amid the economic challenges faced by the congregation due to dependence on the tourism sector and the social dynamics of Bali, the church has great potential to promote economic independence through various programs and initiatives. The main objective of this research is to identify and analyze the church's economic programs, evaluate their impact on the congregation's welfare, uncover implementation challenges, and provide strategic recommendations for improving the effectiveness of future programs. The urgency of this research lies in the need for a relevant and contextual community-based economic empowerment model, given the lack of similar empirical studies in Bali. The novelty of this research lies in the in-depth case study approach with data triangulation from interviews with pastors and congregants, as well as the analysis of active participation and internal church dynamics in managing the economic program. The research methodology uses a qualitative approach with in-depth interviews with church leaders and congregants, participatory observation, and documentation of the church's economic programs. Data were analyzed thematically and verified through source triangulation. The main findings indicate that the church plays a significant role in improving the congregation's economy through skills training, capital assistance, the formation of cooperatives, and the facilitation of business networks. However, the implementation of the program still faces challenges such as limited resources, internal resistance, and market access. The level of congregation participation is a key factor in the success of the program. The research conclusion emphasizes that the church can become an effective agent of economic change if it can innovatively address internal and external challenges. The proposed recommendations include strengthening the church's management capacity, enhancing the financial literacy of the congregation, and developing strategic partnerships with various parties. This research is expected to serve as a reference for churches and other religious institutions in developing community-based economic empowerment programs in various contexts.